Research on the synergizing the reduction of pollution and carbon emissions of new-type urbanization - Yuanyuan Zhao; Hongwei Zhou; Chuanzeng Jiang; Linlin Xuan; Liming Chen (Environmental Research Communications)
Based on the data of 282 Chinese cities from 2011 to 2018, this article analyzes and explains the synergizing the reduction of pollution and carbon emissions (PCE) of new-type urbanization (NTU) by employing the Differences-in-Differences (DID) model. The results exhibit that the NTU has a significant promoting effect on reducing atmospheric pollutant emissions and improving carbon emission efficiency, demonstrating significant synergistic effects in reducing PCE. This effect varies greatly due to differences in city areas, urban-rural income gap and city scale. Mechanism analysis shows that the NTU mainly affects the synergizing the reduction of PCE by promoting land use structure adjustment and enhancing the level of green technology innovation. Further research indicates that the NTU has a great spatial spillover effect on PCE. This article provides a comprehensive exploration and evaluation of the synergizing the reduction of PCE under the NTU policy. The research findings provide policy insights for reducing air pollutants and carbon dioxide emissions, as well as for advancing the construction of NTU more effectively.